A Process to Analyze Ethical Issues of Information Systems - Santoro, Flavia Maria; Costa, Rosa Maria E. Moreira (Anais do Workshop sobre as Implicações da Computação na Sociedade (WICS), 2020)
Contemporary society is going through the so-called Digital Age. In this scenario, information systems (IS) play an essential role in many sectors of society, such as commerce, politics, services, entertainment, information sharing. Although discussions about ethical issues become increasingly necessary, it is not always an easy task. This paper proposes a process to help the IS professional and the citizen in sensitive decision-making contexts, in which conflicts may arise. To justify the definition of this process, we discussed the importance of new technologies based on Andrew Feenberg's philosophy of technology. Finally, we analyze the results of its application in the context of a well-known case in the light of the theoretical foundations.